Green Healthcare Awareness, Attitudes and Practices Among Undergraduate Students - Raikhola, Pushkar Singh (Nepal Journal of Multidisciplinary Research, 2026)
Background: Healthcare sectors are one of the sectors that contribute to environmental degradation through waste generation, energy use, and greenhouse gas emissions, hence the need to inculcate green healthcare practices in future professionals. Objectives: The study aimed to evaluate awareness, attitude, and practice levels in green healthcare among undergraduate Bachelor in Healthcare Management students in Nepal, as well as their associations. Methods: A descriptive cross-sectional study was done among 205 BHCM students using an online structured questionnaire. Analysis was done using SPSS software with a one-sample t-test, ANOVA, and correlation. Findings: BHCM students showed significant awareness above the neutral point for green healthcare (M=3.91, t=18.68, p<.001). No significant differences were found in BHCM students' attitudes based on their faculties of study (F=0.611, p=.544). Moderate positive correlations were found for awareness with practice (r=0.512, p<.01) and practice with advocacy (r=0.569, p<.01). Conclusion: BHCM students showed positive awareness and attitudes towards green healthcare. The moderate positive correlations for awareness with practice indicated a significant knowledge-behavior gap. Implication: It is important for academic institutions to provide experiential learning strategies for healthcare students to change awareness into practice.